Stress corrosion behavior of X80 pipeline steel in natural seawater with different dissolved oxygen (Fracture and Structural Integrity, 2019)
Slow strain rate stress corrosion test of X80 steel in the natural seawater are carried out to study to effect of dissolved oxygen on the sensitivity of stress corrosion. Scanning electron microscope (SEM) combined electrochemical measurement are adopted to analyze mechanism and the influencing factor of stress corrosion cracking. The results show that the sensitivity of SCC in the natural seawater increases, and the stress corrosion cracking gradually transforms from ductile to quasi-brittle fracture, with the increase of dissolved oxygen. Tafle polarization and electrochemical impedance spectroscopy of X80 show that dissolved oxygen aggravates electrochemical corrosion and reduces corrosion resistance. Corrosion pits and micro cracks at the lateral and fracture surface trigger stress concentration and promote anodic dissolution under stress, thereby accelerate the process of stress corrosion cracking of X80 steel in the seawater.
Keywords: Stress corrosion; Dissolved oxygen; Sensitivity; Stress concentration; Anodic dissolution